The Moderation (Wasatiyah) Paradigm in the Malay World: Thoughts of M. Kamal Hassan : Moderation and Thoughts of Kamal Hassan - Islam, Muhammad Hedayatul (Archives of Business Research, 2019)
Kamal Hassan, fondly known as Prof. Kamal is a symbolic academician in a well-versed personality of virtue, adab (good manners), and hikmah (wisdom). He has been accredited as one of the intellectual leaders of Madarasah al-Wasatiyah or movement of moderation and ideologue of Islamization of knowledge in the contemporary Malay world. He is also one of the leading figures in the area of contemporary Islamic thought and Malay civilization. His literature is vocal on the issue of Islam and modernity, Wasatiyah or Islamic moderation, Islamicization of human knowledge, Integrated Islamic education, secularism and secular education, the relationship between East and West, human rights and civil society. His metaphysical views have been often quoted in the literature of Muslim intellectuals and activists in Southeast Asia. Moreover, his philosophical thought of a justly balanced approach of Wasatiyah is also worth mention. The noteworthy highlights in his literature and speech promote Muslim leaders and scholars to examine: what collective moral responsibility they have, as a moderate nation or Ummah Wasat, to build a better world and a better nation—Khaira Ummah. There were many reasons for the intellectual decline of Muslims and the Muslim world. One of the reasons by moving away from the moderate and comprehensive understanding of the Qur’an. There is undoubtedly an urgent need to retract the philosophy of Ummah Wasat based on divine knowledge rooted in humanistic and societal life. Hence, Kamal Hassan fetched the thoughts in his lectures, articles, and books to relevantize the philosophy of moderation in Islam. Keywords: Wasatiyah, Moderation, Justly Balanced Path, Islamization of Knowledge, Kamal Hassan and Malay World.